Интенсивность теплоотдачи при кипении на поверхности малого размера - Alekseik, O. S.; Kravets, V. Yu.; Kopchevskaya, I. A. (PE "Politekhperiodika", Book and Journal Publishers, 2012)
Dependence of heat-release surface of heat carrier (water and ethanol) characteristic size, boundary conditions and thermophysical properties on boiling heat transfer intensity on small-size surface was investigated. Criterion equation for boiling heat transfer coefficients on small-size surface was obtained.